Gastric and Duodenal Pseudomelanosis: An Extended Unusual Finding in a Patient with End Stage Kidney Disease - Noor Ul Ain Qureshi; Muhammad Faraz Younus; Kourosh Alavi; Muhammad Yasin Sheikh (Case Reports in Gastrointestinal Medicine)
Gastric and duodenal pseudomelanosis is a rare endoscopic mucosal finding, characterized by the accumulation of iron in macrophages of the lamina propria of the stomach and duodenum. The clinical significance and long term sequelae have not been clarified yet. However, this benign condition is associated with a variety of clinical conditions, such as essential hypertension, chronic renal failure, diabetes mellitus, long term intake of iron supplements, and furosemide. Duodenal pseudomelanosis appears to be more common than gastric pseudomelanosis given the fact that a few cases of gastric pseudomelanosis have been reported in the literature so far. We report a case of 88-year-old lady with ESRD who is maintained on hemodialysis and presented with abdominal pain. An upper GI endoscopy showed discoloration of the antrum of the stomach and most portion of her duodenum. Histopathology report confirmed the presence of iron laden macrophages in the lamina propria of both stomach and duodenum.